COMPARATIVE LINGUISTIC AND FUNCTIONAL ANALYSIS OF VERBAL IRONY DURING THE COVID-19 PANDEMIC: Using Examples from English and Georgian Facebook Posts - Nikabadze, Mari (Online Journal of Humanities ETAGTSU, 2022)
This paper discusses the function of verbal irony on social media via comparative analysis through the scope of social and cultural peculiarities revealed in social, cultural, religious, and other characteristics of an individual or a group of people. The function is manifested through a shared language, symbols, norms, and values of the population to which they belong. The empirical data cover verbal posts shared on Facebook by English and Georgian users during the 2020 March-April COVID-19 pandemic. The paper discusses the process of decoding irony through its psycho-emotional and functional perception demonstrated in the following components: 1. Background knowledge of the speaker/writer and listener/reader, their general perception of the world, their profession, and place in the social environment (Colston, Katz, 2005); 2. The situational character of irony (Kotthoff, 2003); 3. Insincerity or the effect of allusion pretense (Kumon Nakamura, Glucksberg, Brown,1995) 4. The contrast of the verbal ironic statement with the implied meaning (Sperber and Wilson,1986). From the functional perspective, the study of irony in this paper is based on the following categories suggested by Dui, Caplan, and Verner: 1. Humor 2. The elevation of the social status 3. Aggression, and 4. Emotional control (Dews, Caplan, Winner, 2009). More specifically, the paper aims to explore the following issues:1. How is the function of irony revealed in verbal posts on Facebook? 2. What is the socio-pragmatic function of this figure of speech in virtual reality? 3. Can we trace cultural differences in English and Georgian verbal posts on Facebook during the March-April 2020 pandemic? Full Text (PDF)